Child poverty and regional disparities in Turkey - Eryurt, Mehmet Ali; Koç, Ismet (The Turkish Journal of Pediatrics, 2013)
The United Nations Children's Fund (UNICEF) defines child poverty as the inability of the child to realize their existing potential due to their inability to access resources across different dimensions of life (income, health, nutrition, education, environment, etc.). On the basis of this definition, an attempt has been made in this study to put forth the disadvantaged positions children have in different dimensions of their lives, specifically by taking regional disparities into account. As the data source, the Turkey Demographic and Health Survey 2008 is used, a survey that consists of detailed information about the different dimensions of child poverty. In this study, in order to measure poverty in four different dimensions (education and work, health and nutrition, family environment, and domestic environment), a total of 25 variables were used and descriptive and multivariate analyses were made in order to highlight the regional disparities in child poverty. Principle components analysis conducted through the use of a deficit approach reveals that the variables closely related with education and health and nutrition were the critical dimensions behind child poverty in Turkey. The results of this study indicate that 22.4% of children in Turkey are poor when various dimensions of life are taken into account; the region with the highest child poverty is Central East Anatolia, at 34.9%, while the region with the lowest rate is East Marmara, at 15.6%.